Challenges of older people experienced after an earthquake disaster situation: A neglected issue - Mehdi Abbasian; Morteza Ghojazadeh; Ehsan Sarbazi; Mahla Safaralipour; Hadi Hamishehkar; Hassan Soleimanpour (Journal of Research in Clinical Medicine)
Introduction: Older adults’ problems and needs may be ignored and not considered a priority matter during disasters due to their complexities and differences from other age groups. This content analysis study was conducted to explain the older adults’ experience of living in tents after the Mianeh county earthquake. Methods: In this research, we used a descriptive qualitative approach. The key elements of Standards for Reporting Qualitative Research (SRQR) were applied to design the research. Data were collected in-depth and semi-structured interviews were done with potential eligible participants. We used heterogeneous purposive sampling (with a maximum variety of 16 older adults with ages in the range of 60–81 years in Mianeh, East Azerbaijan, Iran. The data were analyzed using the conventional content analysis technique. Results: Four main categories emerged, including failure to provide basic physiological needs, poor management of public support, distress and survival attempts, and loss of life authority. The main themes extracted included psychological quality of life and meeting the basic needs (disabilities and inefficiencies). Conclusion: It is beneficial to consider the specific needs of vulnerable groups, such as the elderly population, during the program designing by counties’ crisis management teams.